Application of multivariate statistical techniques for water quality characterization of Sarda Sagar Reservoir, India - Kumar, Prem; Saxena, K K; Singh, N Okendro; Nayak, Ashok K; Tyagi, B C; Ali, S; Pandey, N N; Mahanta, P C (Indian Journal of Fisheries, 2012)
Multivariate statistical techniques were applied to water quality dataset collected from Sarda Sagar Reservoir. The resultsrevealed the usefulness of multivariate techniques for evaluation of input water sources and interpretation of large complexwater quality dataset for effective management of water resources. The largest source of variation (25%) is contributed fromphysical water quality parameters. Additional inputs come from the second factor accounting for about 15%. The thirdfactor, accounting for 14% is associated with wastewater discharges and the fourth factor accounting for 12%. Finally, itsuggests that a fraction of wastewater discharge is the only primary source of variations in this reservoir and there is no majorthreat of pollution. Cluster analysis showed that number of sampling sites as well as the sampling frequency could beconsolidated.